Contract Theory and Human Dignity Response to :: Kant and Contemporary Moral Philosophy by Friedo Ricken (The Macau Ricci Institute Journal, 2022)
In his article “Kant and Contemporary Moral Philosophy” Professor Friedo Ricken discusses the influence of Kantian philosophy on contemporary moral philosophy. It involves not only Kant’s relations with consequentialism, deontology and various representatives of virtue theory, but also the understanding and interpretation of Kant by contemporary ethicists. What interests me most is the connection Ricken recognizes between Kant and contract ethics.In the context of normative ethics, the theory of contract, which regards contract as the starting point of moral argument, is undoubtedly an important theoretical framework. The ethics of contract theory understands morality as a rational design or wise contract made by human beings for the protection of interests and the satisfaction of needs. Such a contract reflects the moral implication of taking into account the equal status of the subject of action and respecting its independent will. The theory of contract regards morality as a cooperative behavior between actors for the mutual protection of interests, which enables the society to achieve maximum justice.